Analysis of Long-Term Relationship between Spot and Futures prices Using Johansen’s Test of Cointegration - Debasish, Sathya Swaroop (Information Management and Business Review, 2011)
The main objective of the study is to examine the long-term relationship between spot prices and futures prices A. The study has used daily prices (closing, opening, high and low) in both spot market and futures market for the 40 sample individual stocks drawn from six leading sectors namely, Automobiles, Banking, Cement, Gas, Oil & Refineries, Information Technology and Pharmaceutical. The period of study is from 1st January 1997 to 31st May 2009. The study begins by testing the stationarity of the spot price series and futures price series using two econometric methods namely, Philips Perron (PP) test and Augmented Dickey-Fuller (ADF) test. The long term relationship between spot prices and futures prices is statistically tested using Johansen’s test of Cointegration employing likelihood Ratio (L.R.), under the hypothesis that there exists a single cointegration equation between spot and future prices. It is found that both spot prices and futures prices for the selected companies are not stationary in the level form, but there is evidence of stationarity in the first difference form. The study finds a single long-term relationship for each of the selected companies across the six sectors. Among the selected companies in each sector, those evidencing strongest relation in respective sector are Tata Motors, Punjab National Bank, Gujrat Ambuja Cements, Bongaigaon Refineries, I-Flex and GLAXO Pharma.